“If the river comes to an end, the community comes to an end”: pedagogical dimension of environmental racism - André Carneiro Melo; Marco Antonio Leandro Barzano (Praxis & Saber)
This article aims to analyze the educational practices that emerge from conflict situations in which ancestry and the right to the quilombola territory are appreciated. From the narratives of the residents of the Barreiros de Itaguaçu community with regard to the conditions of retrenchment of their traditional territory, we wanted to contribute—through the production of knowledge about the environmental racism experienced by the community—with the hope of increasing its visibility in places where the different axes of coloniality do not allow it. Living together within the community revealed that the residents create resistance strategies to fight the process of occupation of their territory. This idea of resistance that we describe here is not limited exclusively to the defense of the territory, it also refers to the defense of the ways of survival and to the defense of the community way of life, which evinces the quilombola identity. This context of community resistance is considered as a universe of tensions and diverse problems engendered by the worldwide colonial system, based on the different faces of coloniality, from where the quilombola community-produced knowledges emerge, which query other ways of appropriating nature.